Slovenci in znanost - Ivanišin, Marko (Teorija in praksa, 2008)
In this article, we used empirical data from Slovene public opinion survey (SJM) and Eurobarometer survey (EB) to sketch the relationship of Slovenes towards science and technology. The sketch was based on conclusions made by confronting data of same and similar questions in SJM 1987, 1995, 1999 and EB 2005. On the side, we came to twofold conclusions. On the one hand, most results from surveys support in Slovenian scientific literature dominant paradigm that (Slovene) public is increasingly sceptic toward once absolutely positive attitude toward science and technology. On the other hand, several results deny this theory and show that Slovenes trust science more and more (resp. trust less and less in faith, intuition, and politics).
Keywords: Science; Znanost; Technology; Tehnologija; Javnost; Public; Public opinion; Javno mnenje; Slovenci; Slovenes; Slovensko javno mnenje